Black American Maternal Prenatal Choline, Offspring Gestational Age at Birth, and Developmental Predisposition to Mental Illness. (13th November 2020) - Hunter, Sharon K; Hoffman, M Camille; McCarthy, Lizbeth; D'Alessandro, Angelo; Wyrwa, Anna; Noonan, Kathleen; Christians, Uwe; Nakimuli-Mpungu, Etheldreda; Zeisel, Steven H; Law, Amanda J; Freedman, Robert
Abstract: Black Americans have increased risk for schizophrenia and other mental illnesses with prenatal origins. Prenatal choline promotes infant brain development and behavioral outcomes, but choline has not been specifically assessed in Black Americans. Pregnant women ( N = 183, N = 25 Black Americans) enrolled in a study of prenatal stressors and interactions with prenatal choline. Black American women had lower 16-week gestation plasma choline than Whites. Lower choline was not related to obesity, income, or metabolic genotypes. Pregnant women in rural Uganda have higher choline levels than Black American women. Black Americans' lower choline was associated with higher hair cortisol, indicative of higher stress. Lower maternal choline was associated with offsprings' lower gestational age at birth and with decreased auditory P50 inhibition, a marker of inhibitory neuron development. Behavioral development was assessed on the Infant Behavior Questionnaire-R-SF (IBQ-R) at 3 months. Lower Black American maternal gestational choline was associated with lower infant IBQ-R Orienting/Regulation, indicating decreased attention and relation to caregivers. Additional evidence for developmental effects of choline in Black Americans comes from a randomized clinical trial of gestational phosphatidylcholine supplementation versus placebo that included 15 Black Americans. Phosphatidylcholine increased gestational age at birth and newborn P50 inhibition and decreased Social Withdrawn and Attention problems at 40 months of age in Black Americans' offspring compared to placebo. Inhibitory and behavioral deficits associated with lower prenatal choline in offspring of Black American women indicate potential developmental predispositions to later mental illnesses that might be ameliorated by prenatal choline or phosphatidylcholine supplementation.